2023
DOI: 10.15237/gida.gd23019
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Lactic Acid Bacteria From Traditional Pickle Samples, Their Identification Using Molecular Methods, and Determination of Some Functional Properties

Abstract: Bu çalışmada ülkemizin farklı illerinden toplanmış 17 adet geleneksel turşu örneğinden Laktik Asit Bakterileri (LAB) izole edilip tanımlanmış ve izolatların fonksiyonel nitelikleri karakterize edilmiştir. Genotipik ayrıştırma sonucunda 9 farklı türe ait 21 suş tespit edilmiştir. Takiben bu 21 suşun potansiyel probiyotik değerlendirmeleri safra tuzlarına direnç ve düşük pH’da gelişim açısından test edilmiş ve Lactiplantibacillus plantarum ve Levilactobacillus brevis suşlarının yüksek canlılık gösterdiği tespit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…As a result of genotypic differentiation, 21 strains belonging to 9 different species were identified. It was stated that Lactobacillus plantarum strain was more numerous [18]. It was observed that the distribution of lactic acid bacteria species in pickle samples was similar to the studies [11,13,15,17].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As a result of genotypic differentiation, 21 strains belonging to 9 different species were identified. It was stated that Lactobacillus plantarum strain was more numerous [18]. It was observed that the distribution of lactic acid bacteria species in pickle samples was similar to the studies [11,13,15,17].…”
Section: Discussionsupporting
confidence: 67%
“…Yıldız [13] Reported the pH values of pickle samples as pH 3.51 in the range of 3.39-3.96 and the average pH as 3.51 and the amount of salt in the range of 1.25-5.11% and the average amount of salt as 3.66%. İspirli and Dertli [18]. Stated that the pH values in pickle samples were in the range of 2.97-6.67.…”
Section: Discussionmentioning
confidence: 99%